Legal Analysis of Default Dispute Resolution in Money Lending and Borrowing Agreements with Fiduciary Guarantees for Certain Individuals in the City of Mataram - Kazwaeni; Hj. Rodliyah; Aris Munandar (MultiTech Publisher, 2025)
This study aims to examine the resolution of breach of contract disputes in loan agreements with fiduciary guarantees among certain individuals in Mataram City. It covers the implementation of loan agreements with fiduciary guarantees as well as the methods and processes involved in resolving breach of contract disputes in such agreements, specifically in the Sekarbela District of Mataram City. The research also seeks to determine whether the dispute resolution and its implementation comply with legal mandates. This study employs a normative-empirical legal research approach, utilizing statutory, conceptual, and sociological approaches. The research findings indicate that loan agreements with fiduciary guarantees do exist among certain individuals. Observations conducted so far reveal that such practices are common; however, their implementation often involves minor errors that can have significant consequences in cases of breach of contract. One of these errors is the failure to register the fiduciary guarantee with the Fiduciary Registration Office, which results in legal uncertainty and the emergence of preferred creditors. Additionally, some loan agreements are made without collateral, which could ultimately harm the creditor.